Analisis Alih Kode dan Campur Kode Novel Jangan Pergi Lara Karya Mira W - Addiny Nur Azizah; Ita Kurnia; Elsiana Rahmawati; Putri Yessa Rahmawati (Dharma Acariya Nusantara: Jurnal Pendidikan, Bahasa dan Budaya, 2024)
The aim of this research is to analyze the forms of code switching and code mixing in the novel "Don't Go Lara" by Mira W. This research uses qualitative research methods. The qualitative type chosen is descriptive. This type was chosen because research data is described descriptively which requires solving based on existing data, analyzing and interpreting. It is impossible for language variations to occur in a society because there are no differences between people. Sociolinguistics is concerned with the use of a particular language, while sociology focuses on the social factors that influence a language or dialect. The focus of analysis in the field of sociolinguistics is who speaks, what language is used, to whom it is spoken, when and for what purpose it is spoken, and what the topic of conversation is. Dedi was standing on the other side of the road. Lara waved at him. "yesss...!" Dedi exclaimed while jumping high with joy. Based on the dialogue, it shows that the word yes comes from English which means yes. So it can be concluded that the word yess is a form of code switching from Indonesian to English. “Heru is not a profiteer! He's a salesman!” Based on the dialogue excerpt, it shows that there is a mixing of two languages ​​in one sentence, namely Indonesian and English. So it can be concluded that someone can use two languages ​​in one dialogue or can be called code mixing.